2019
DOI: 10.1016/j.jdent.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial on the survival of lithium disilicate posterior partial restorations bonded using immediate or delayed dentin sealing after 3 years of function

Abstract: ObjectivesThe survival and success rate and the quality of survival of partial ceramic restorations bonded employing Immediate (IDS) or Delayed Dentin Sealing (DDS) in vital molar teeth were evaluated in a randomized clinical trial with within-subject comparison study.Materials and Methods 30 patients received two lithium disilicate ceramic (IPS-e.max press, Ivoclar Vivadent) partial restorations on vital first or second molar teeth (N=60). The two teeth randomly received either IDS (test group, n=30) or DDS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 29 publications
1
55
0
6
Order By: Relevance
“…Significant differences among the conditioning methods tested were not observed. van der Breemer et al 2019 148 Randomized clinical trial Survival, success rate, and quality of survival of partial ceramic restorations Investigated the survival, success rate, and quality of survival of partial ceramic restorations (IPS e.max) in vital molars bonded using IDS (Clearfil SE Bond + Clearfil Majesty Flow) after 3 years of function. Ceramic restorations with IDS did not yield differences in the success rate or survival rate after 3 years of function.…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences among the conditioning methods tested were not observed. van der Breemer et al 2019 148 Randomized clinical trial Survival, success rate, and quality of survival of partial ceramic restorations Investigated the survival, success rate, and quality of survival of partial ceramic restorations (IPS e.max) in vital molars bonded using IDS (Clearfil SE Bond + Clearfil Majesty Flow) after 3 years of function. Ceramic restorations with IDS did not yield differences in the success rate or survival rate after 3 years of function.…”
Section: Resultsmentioning
confidence: 99%
“…134 Two randomized clinical trials published after 2015 with indirect posterior restorations did not observe any difference in success rate or post-luting sensitivity at 3 years when they compared the IDS technique with the conventional luting technique. 135,136 The 11-year results of a clinical trial with porcelain veneers on anterior teeth at 11 years found an increase in success rate from 81.8% to 96.4% using the IDS technique when the area of exposed dentin was above 50%. 137 6 | UNIVERSAL COMPOSITE RESINS Due to their considerable particle size, classical macrofilled composite resins did not polish well.…”
Section: Immediate Dentin Sealingmentioning
confidence: 99%
“…Afterward, 2760 studies were excluded following reviewing the titles and abstracts, leaving a total of 30 articles to be assessed by full-text evaluation. From these, 8 studies were not considered for the qualitative analysis for various reasons: 4 were clinical studies [ 18 , 19 , 20 , 21 ], 2 studies did not evaluate bond strength [ 22 , 23 ], and in 2 studies, there was not a control group using DDS [ 24 , 25 ]. Thus, a total of 22 studies were considered in the qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%